(untitled) (Research, Society and Development, 2026)
Despite the Military Fire Brigade’s excellence in physical risk control, the emotional impact derived from incidents highlights the need to improve the management of emotional reactions as a complement to the operational focus. The objective of this study was to analyze the applicability of Psychological First Aid (PFA) as a strategic tool in the operational service of the Military Fire Brigade. A qualitative bibliographic review was conducted in academic databases and institutional repositories, using specific descriptors and a timeframe from 1991 to 2021, correlating crisis intervention fundamentals with contemporary operational doctrine. The results indicated that the adoption of communication and support strategies mitigates the impact of acute stress and ensures the effectiveness of the operational outcome. It is concluded that PFA training is an essential tactical resource that enhances the excellence of service and scene management by the organization.